Letramento digital de professores de Língua Portuguesa: cenários e possibilidades de ensino e de aprendizagem com o uso das TDIC - Josiane Brunetti Cani (2019)
The teaching of Portuguese demands develop skills and strategies to deal with the teaching and learning of reading and writing in digital social practices. Recognizing the relevant role the teacher plays in such a context, the objective of this research is to find out if there is a relationship between those professionals´ personal digital literacy profiles and the professional one, as well as the implementation of digital information and communication technologies in their pedagogical practices. Contributions are presented on studies on educational technological resources, those of the teacher and of the school curriculum in virtual environment, as well as of documents such as the National Curricular Common Base and the Common European Framework of Digital Competence. The conceptual framework presents skills for teaching in the 21st century, as well as it introduces the expressions "digital literacy" and "digital competence", with different theoretical-methodological perspectives. Next, text presents the components necessary for the teachers´ technological knowledge, namely: (a) the level of teachers proficiency through the European Framework of Digital Competence for Educators; and (b) the relationship between digital technologies and pedagogical practices through the Technological Pedagogical Knowledge of Content, the Substitution, Extension, Modification and Redefining Method and the Digital Competence Model for Teachers. Fifty-seven teachers from municipal, state and federal schools collaborated to this study. They answered a semi-structured questionnaire, which allowed for delineating their digital literacy profiles, both personal and professional. Of those teachers, 29 participated in a focus group and in a training course for the use, enhancement and diversification of digital technologies for teaching purposes. Data analysis showed that: (a) with regard to the personal digital literacy profile, teachers at municipal and state schools have difficulties in adapting the digital technologies for personal purposes, while those of the federal schools use such resources more accurately; (b) as to the professional profile, in spite of performing some activities with digital technologies, the participants are still in an embryonic phase for a digital technology practice which can duly follow the social transformations; (c) teachers use digital technologies as traditional teaching tools such as editors to type pre-built text on paper and software to prepare lessons with slides; and (d) teachers recognize the importance and possibility of more interactive classes with the use of digital information and communication technologies. These results allow to the conclusion that dealing with technological resources for personal use does not necessarily enable teachers to employ them in the classroom. Therefore, some specific training, which allows them for using digital technologies in their pedagogical practices, is needed.